Finite elements : computational engineering sciences - Baker, A. J., 1936- (Hoboken : Wiley, 2012)
Approaches computational engineering sciences from the perspective of engineering applications Uniting theory with hands-on computer practice, this book gives readers a firm appreciation of the error mechanisms and control that underlie discrete approximation implementations in the engineering sciences. Key features: Illustrative examples include heat conduction, structural mechanics, mechanical vibrations, heat transfer with convection and radiation, fluid mechanics and heat and mass transportTakes a cross-discipline continuum mechanics viewpoi.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Finite element method; Finite element method; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; Finite element method; Electronic books; Electronic books